Socio-Economic Impacts of “Ῑd-Al-Adhā” (Festival of Sacrifice) for the People of Odeda Local Government of Ogun State, Nigeria - Ahmad, Abdulganiy Kayode (NIU Journal of Social Sciences, 2022)
This study investigated socio-economic impacts of â€˜á¿™d-al-adhÄ (festival of sacrifice) for the people of Odeda Local Government of Ogun State, Nigeria. The study adopted the descriptive research design of a survey type where a self-designed questionnaire was used to collect data. The entire Muslims of Odeda Local Government Area of Ogun State constituted the population of the study. A sample of four hundred (400) respondents was selected for this study using stratified and convenient sampling techniques. Of the 400 copies of the questionnaire administered, 385 were returned, indicating 96.5% response rate. Data obtained were analysed, using frequency counts, simple percentage, and bar charts. Findings from the study revealed that to a large extent, Muslims in Odeda Local Government Area of Ogun State have understanding of the concept of â€˜á¿™d-al-AdhÄ. Findings also indicated both positive and negative social and economic impacts of â€˜á¿™d-al-AdhÄ for the lives of Muslims in Odeda Local Government Area of Ogun State. Based on the findings from this study, it was recommended among others that government should be more pro-active in eliminating the exploitation and extortion of innocent buyers by some traders and service providers during á¿™d-al-AdhÄ, and that Imams and Muslim organisations should make use of the media (print, electronic and mass media) to address the various anti-social and immoral acts exhibited by some people during á¿™d-al-AdhÄ. Keywords: á¿™d-al-AdhÄ, Social, Economic, Anti-Social Behaviour.